Cluster activities in different institutional environments. Case studies of ICT-Clusters from Austria, Germany, Ukraine and Serbia - Anastasiia Konstantynova; Tine Lehmann (European Regional Science Association (ERSA), 2016)
In recent decades industrial clusters and agglomerations were recognized as drivers of regional and often national economic growth and competitiveness. Based on this cluster policy has been widely used to spur economic change, especially on the sub-national level. The public support to cluster development was widely done following the observed examples in the United States aiming to follow their success stories. Most commonly applied cluster policy approach composed of cluster mapping, establishment of institutions (labelled as cluster initiative/ association) in respective clusters through public-private support of these institutions and companies activities. However, the implementation of blue-printed cluster policy did not always lead to positive paths of cluster development due to the negligence of country / region specific institutional frameworks. This paper fills this void, by exploring selected cases of cluster associations and how their activities are influenced by different sets of institutional framework conditions. Information and communication technologies (ICT) clusters and their associations in European Union (EU) and Non-EU countries are taken as cases for the analysis.
Keywords: R11; R58; O18; M21; 330; clusters; cluster policy; cluster association; institutions; ICT